2016
DOI: 10.1515/afe-2016-0109
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of Friction of a Brake Disc-Brake Pad Friction Couple

Abstract: The paper concerns evaluation of the coefficient of friction characterising a friction couple comprising a commercial brake disc cast of flake graphite grey iron and a typical brake pad for passenger motor car. For the applied interaction conditions, the brake pressure of 0.53 MPa and the linear velocity measured on the pad-disc trace axis equalling 15 km/h, evolution of the friction coefficient μ values were observed. It turned out that after a period of 50 minutes, temperature reached the value 270°C and got… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The friction coefficient for brake materials is required in the range of 0.3–0.45 as per the industry standards and published results. 2426 Therefore, based on the results, it is concluded that Sample A shows better coefficient of friction with minimum material loss among other compositions of friction modifiers. This is mainly attributed to the presence of graphite which helps in the regulation of self- supporting layer over the sample surface under sliding action at the constant speed and load which act as a protective layer on the surface because of its lubricity nature under action of sliding at the contact and it is also due to high hardness than other samples (as shown in Figure 7).…”
Section: Resultsmentioning
confidence: 89%
“…The friction coefficient for brake materials is required in the range of 0.3–0.45 as per the industry standards and published results. 2426 Therefore, based on the results, it is concluded that Sample A shows better coefficient of friction with minimum material loss among other compositions of friction modifiers. This is mainly attributed to the presence of graphite which helps in the regulation of self- supporting layer over the sample surface under sliding action at the constant speed and load which act as a protective layer on the surface because of its lubricity nature under action of sliding at the contact and it is also due to high hardness than other samples (as shown in Figure 7).…”
Section: Resultsmentioning
confidence: 89%
“…Castings accompany man for about five thousand years [1], and the modern casting technologies are considered as basic methods of production both of elements of various machines and devices, as well as other items, for example artistic ones or the products used in medicine [2][3][4][5][6]. Both the materials, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…8 Voldrˇich 9 established a two-dimensional finite element model of disk and calculated the temperature field and stress field during the braking process by means of numerical analysis. Or1owicz et al 10 used ABAQUS to simulate the influence of different coefficients of friction on the fluctuation of braking torque, indicating that the coefficient of friction would change during the braking process, resulting in the fluctuation of normal force and tangential force on the surface of the brake disk. Mahmoudi et al 11 used functionally gradient materials to solve the problems of fast aging, early wear, thermal crack, and brake decay caused by thermal shock.…”
Section: Introductionmentioning
confidence: 99%